2006
DOI: 10.3168/jds.s0022-0302(06)72459-6
|View full text |Cite
|
Sign up to set email alerts
|

Cheese pH, Protein Concentration, and Formation of Calcium Lactate Crystals

Abstract: The occurrence of calcium lactate crystals (CLC) in hard cheeses is a continual expense to the cheese industry, as consumers fail to purchase cheeses with this quality defect. This research investigates the effects of the protein concentration of cheese milk and the pH of cheese on the occurrence of CLC. Atomic absorption spectroscopy was used to determine total and soluble calcium concentrations in skim milk (SM1, 8.7% total solids), and skim milk supplemented with nonfat dry milk (CSM1, 13.5% total solids). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Chemical elementary analysis of crystals through an X‐ray detector coupled to SEM showed that they are formed of oxygen, carbon, calcium and phosphate. Agarwal et al. (2006) stated that the soluble form of calcium (in cheese) can readily combine with lactate (from lactose fermentation) to form calcium lactate, and as the calcium lactate concentration exceeds saturation; microcrystals of calcium lactate (or more specifically, calcium lactate pentahydrate) are formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical elementary analysis of crystals through an X‐ray detector coupled to SEM showed that they are formed of oxygen, carbon, calcium and phosphate. Agarwal et al. (2006) stated that the soluble form of calcium (in cheese) can readily combine with lactate (from lactose fermentation) to form calcium lactate, and as the calcium lactate concentration exceeds saturation; microcrystals of calcium lactate (or more specifically, calcium lactate pentahydrate) are formed.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of chemical elementary composition and appearance (bright white areas), crystals formed in dehydrated samples of Oaxaca cheese could be calcium lactate crystals. According to Agarwal et al. (2006), some calcium monohydrogen phosphate is also formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing solute (salt, ions, FAA) concentration in the cheese water phase may give rise to aggregation and crystallization phenomena that result in the different types of structures in the interior and on the surface of different cheese varieties observed by some authors (Bianchi et al, 1974;Agarwal et al, 2006a;Tansman et al, 2015). Although the earliest studies date back to the 1900s (Babcock et al, 1903;Tuckey et al, 1938), a clear and unambiguous characterization of these structures has not yet been achieved.…”
Section: Introductionmentioning
confidence: 93%
“…Short time from catch to chemical treatment and short storage time, appropriate chemical treatment, and low storage temperature could slow down the formation and growth of white spots (Mikkelsen et al, 1997). The crystallisation of calcium lactate in hard cheeses during storage was also perceived as a quality defect (Agarwal et al, 2006). Besides, free amino acids such as tyrosine (Tyr) and phenylalanine (Phe) were also found to cause white spots, which resulted from the proteolysis of proteins by moulds on the soybean substrate (Chiou et al, 1997).…”
Section: Introductionmentioning
confidence: 99%